THE EFFECT OF THE COLLABORATIVE PROBLEM SOLVING ON MATHEMATICS LEARNING RESULT REVIEWED FROM THE ABILITY OF MATHEMATICS LITERACY OF CLASS VII - Inova Aulia Martuti (Universitas Ahmad Dahlan, 2020)
This research aims to determine the effect of Collaborative Problem Solving (CPS) learning models on learning outcomes in students' mathematical literacy abilities. This research is included in an experimental study. This study's population was VII grade students of Junior High School (SMP) Muhammadiyah 3 Depok in 2019/2020 consisting of 4 classes. Using random sampling techniques, the sampling technique obtained class VII D as an experimental class and VII-A as a control class. Based on the variance analysis, there is no influence of learning model factors, the interaction of learning models, and inter-student mathematical literacy abilities on mathematics learning outcomes in class VII students of SMP Muhammadiyah 3 Depok.